1998
DOI: 10.1111/1468-2273.00093
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Contemporary Student

Abstract: Is contemporary student life stressful? And if so, what factors are associated with stress among students? This paper attempts to provide answers to these questions in reporting a research project that explored physical and mental health among students studying at Newcastle University in 1995. Forty-nine per cent of a stratified random sample of students (956 students) completed a postal questionnaire which, as well as addressing questions of health, covered numerous aspects of student living conditions and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 7 publications
1
21
0
7
Order By: Relevance
“…In most studies using a transactional framework, outcomes are couched in negative terms, particularly in relation to anxiety and depression (e.g. Lustman et al, 1984;Humphrey et al, 1998), although 'satisfaction' is sometimes included, and particularly in relation to occupational stress (Winefield, 1993). We would suggest that both positive and negative outcomes, and the interaction or balance between them, should be considered in this theoretical framework.…”
Section: Downloaded By [University Of Sheffield] At 18:21 13 October mentioning
confidence: 99%
See 3 more Smart Citations
“…In most studies using a transactional framework, outcomes are couched in negative terms, particularly in relation to anxiety and depression (e.g. Lustman et al, 1984;Humphrey et al, 1998), although 'satisfaction' is sometimes included, and particularly in relation to occupational stress (Winefield, 1993). We would suggest that both positive and negative outcomes, and the interaction or balance between them, should be considered in this theoretical framework.…”
Section: Downloaded By [University Of Sheffield] At 18:21 13 October mentioning
confidence: 99%
“…What impact combined role demands or stressors have for those who have to manage multiple roles of full-time education and term-time employment clearly needs to be explored further, taking account of the negative and positive contributions towards students' psychological well-being at different career stages (Humphrey et al, 1998;…”
Section: Positive and Negative Psychological Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…Released from the oversight of parents, but not yet immersed in adult roles, 18-to 25-year olds tend to engage in activities exploring alternatives more intensely than they did as teenagers [6]. This is a time for experimentation [7][8][9], it is also a pressurised timesocially, financially and academically [10,11]. In a recent review of the literature, researchers identified levels of prescription stimulant use amongst American undergraduates to range between 1.5 and 31%, most commonly as a study tool to improve attention [12].…”
Section: Introductionmentioning
confidence: 99%